Human-AI Collaboration in Curriculum Reform: A Posthuman Investigation into AI Driven Class in Chinese University - Wang, Haitao; Zhao, Hangxuan; Li, Yiwei; Zhang, Hailong (Journal of Posthumanism, 2025)
As artificial intelligence (AI) technologies become increasingly integrated into higher education, university instructors are compelled to navigate shifting pedagogical landscapes and reconfigure their professional identities. This qualitative study investigates how university teachers in China perceive and negotiate their roles in AI-mediated classrooms, using a posthumanist theoretical framework to explore human–machine entanglements in pedagogy. Drawing on semi-structured interviews with six instructors across diverse disciplines, the study identifies three emergent orientations toward AI: as an assistant, a collaborator, and a threat. The study demonstrates how AI integration provokes both pragmatic adaptation and deep-seated identity renegotiation, underscoring the affective, ethical, and epistemological tensions of educational transformation.